RUANG HUNIAN DAN KREATIF ANAK-ANAK YATIM PIATU - Gavin Hanli Lim; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2023)
As of September 2021, the Ministry of Social Affairs received reports that the number of orphans had reached 28 thousand people which was caused by the main impact, namely Covid-19. The DKI Jakarta Provincial Government held a meeting and stated openly about the number of people who died of more than 13 thousand people and resulted in 9 thousand children in Jakarta becoming orphans or orphans. As orphans who are also affected by Covid-19, some have received assistance and have foster parents. But this does not mean that the problem has been solved. In terms of empathy with the suffering of orphans, emotional contagion will evoke an intense state within oneself, just as someone who is experiencing distress by softening the boundaries between himself and others. Modern empathetic architectural design focuses on design that engages the community. An understanding of how the built environment will have an impact on social change. Establish design with past and future societies in a close relationship. Orphans are included in the category of vulnerable children or children who need special protection (children in need of special protection). They are said to be neglected because their basic needs are not met spiritually, physically, or socially. The Covid-19 pandemic has had a huge impact on all sectors of life. The death toll from the corona virus is still falling to this day. Orphans often have stunted physical growth due to their inadequate nutritional needs. In addition to psychological barriers, orphans also experience emotional barriers. In healthy families, children will fear that their parents